Karakteristik Morfologi Serangga Yang Berpotensi Sebagai Hama Pada Perkebunan Kelapa (Cocos nucifera L.) di Desa Tirta Kencana Kecamatan Makarti Jaya Kabupaten Banyuasin - Esti Rahayu; Syamsul Rizal; Marmaini Marmaini (Universitas PGRI Palembang, 2021)
ABSTRACKThe insect morphology research coconut (Cocos nucifera L.) in Tirta Kencana village, Makarti Jaya district, Banyuasin regency was conducted in April-Mei 2021. The research objective was to determine the morphology of insect pest on coconut plants (Cocos nucifera L.) in Tirta Kencana village. This study uses a purposive sampling method, that are three capture methods (insecting net, fitfall trap, light trap). The observation parameters include the type of head, mouth, antennae,wings and legs. The results of the study obtained 123 insects from 6 orders, 9 species. The insects that have potential as the pests consist of 2 orders and 5 species, there are Apogonia expeditionis, Orycthes rhinoceros, Oxya chirensis, Rhynchophorus ferrugineus and Valanga SP. Biting-chewing mouth type, 2 head types, namely Prognatus and Hypognatus, Lamellate and Filiform antenna types, Hard and Straight wing types, Cursorial and Saltatorial leg types.Keywords : Coconut Plants (Cocos nucifera L.), Insect Pests, Morphological Characteristics.